Educational challenges of family caregivers of vegetative state patients for home care preparedness: A qualitative content analysis - Aliakbar Keykha; Monir Ramezani; Shahram Amini; Hossein Karimi Moonaghi; Azadeh Saki (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Patients with a vegetative state (VS) are completely dependent on caregivers in all physical aspects of their lives. Caring for such patients comes with a great deal of difficulty for family caregivers. As a result, family caregivers must be fully trained and prepared for this role. The present qualitative study was conducted to investigate the educational challenges faced by family caregivers of VS patients for home care preparedness. MATERIALS AND METHODS: The present qualitative study was conducted through the conventional content analysis method from August 2020 to September 2021 in two provinces of Iran (Sistan and Baluchestan Province; and Razavi Khorasan Province). Fourteen family caregivers of patients in a VS were included in the study. Semi-structured and in-depth interviews were employed to collect data. The Graneheim and Lundman method was utilized to conduct the data analysis using MAXQDA2020 software. Data collection continued until data saturation and the identification of main categories. RESULTS: As indicated by the data analysis, three categories of "unmet educational needs," "confused caregiver," and "searching for practical knowledge" which included 19 sub-categories described the experiences of family caregivers of patients in a VS concerning challenges they went through in preparation for patient care at home. Participants' experiences revealed that despite the inadequacy of educations provided by health-care providers on knowledge and skills required by family caregivers, they were committed to caring for the patient and trying to acquire the required knowledge. CONCLUSION: Results indicated that inadequate education and the lack of family caregivers' contribution to caring for the patient in the VS during their stay in the hospital impedes their acquisition of adequate knowledge and skill to care for patients at home. Therefore, healthcare system policymakers should be planning to eliminate the educational barriers faced by family caregivers and expand the educational activities of hospitals' homecare centers to provide educational support of family caregivers after the patient's discharge.